Analysis of Carbohydrates, Proteins, And Free Amino Acid Content In Pollen Of Some Crop Plants o f the Family Poaceae. - Urade B.R; Margonwar A.S (The Bioscan, 2025)
The present paper deals with the analysis of carbohydrates, protein, and free amino acid contents in pollen of some genera of the family Poaceae. The plants under investigation were Pennisetum glaucum Oryza sativa , Sorghum bicolor , Zea mays , and Triticum species. The biochemical analysis of some crop plants was performed by standard methods. Detection of carbohydrates was done by the Benedict test, Fehling’s test. and estimation of protein was done by the Bur ette test, xanthoproteic tests.Amino acids were separated and identified by the thin layer chromatographic method. Among all the species, the highest number of carbohydrates was found in Oryza sativa . The highest number of proteinswas found in Pennisetum g laucum , while the highest number of amino acids was found in Sorghum bicolor (15), followed by Triticum species(14), Zea mays (11), Pennisetum glaucum (11) and Oryza sativa (10). Thus, this investigation indicates that carbohydrates, proteins and essential free amino acids were present in all examined taxa of the family Poaceae. It shows that it has nutritional value.